Narrative as Lived Experience - Wesley-Esquimaux, Cynthia (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2010)
My concern is these serious issues will continue to worsen, as a domino effect that our Ancestors have warned us of in their Prophecies (Arvol Looking Horse, May 2010). Aboriginal peoples have walked a long way through a landscape of loss and determination since early contact with Europeans. Today Indigenous authors, healers and spokespeople are asking our people to awaken fully and begin the process of reviving and practicing the seven sacred values that guided our ancestors and ensured that we might live today. The Prophesies and Creation stories contain the encouragement our people need to unburden themselves of deeply embedded historic trauma and loss. We have work to do; to tell our own stories, to actively participate in rescripting the narrative of our lives and representations, and to do this in our own voices (Nissley, 2009). This paper is a narrative of the historic challenges that have shadowed the many since ‘his-story’ began interspersed with the story of my own lived experience.